2015
DOI: 10.1556/imas.6.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of traumatic and non-traumatic peripheral vascular lesions with Onyx

Abstract: Abstract:Purpose: The aim of our study is to verify the feasibility and the effi cacy of Onyx as embolization agent in the treatment of traumatic and non-traumatic peripheral vascular lesions. Materials and Methods: In the period between September 2006 and March 2012, we treated with Onyx 26 patients (14 males/12 females; age range, 18-85 years old; mean age, 65 years old), 11 of which with traumatic peripheral vascular lesions and 15 with non-traumatic vascular lesions (9 neoplastic hemorrhagic lesions, 3 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
6
17
0
Order By: Relevance
“…It is categorized as a non-absorbable, non-adhesive, permanent liquid embolic agent that may be used off-label for both small and large vessels (2). These features making EVOH copolymer effective in treating cerebrovascular lesions may benefit peripheral applications, which explain why its use is becoming more widespread among interventional radiologists in the treatment of peripheral lesions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, Onyx  is still perceived by some interventional radiologists as an expensive and complex embolic agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is categorized as a non-absorbable, non-adhesive, permanent liquid embolic agent that may be used off-label for both small and large vessels (2). These features making EVOH copolymer effective in treating cerebrovascular lesions may benefit peripheral applications, which explain why its use is becoming more widespread among interventional radiologists in the treatment of peripheral lesions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, Onyx  is still perceived by some interventional radiologists as an expensive and complex embolic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Being a non-adhesive agent, it allows precise positioning and control of the tip of the delivery microcatheters during the EVOH injections. The Interventionalist can interrupt the injection, reanalyze the EVOH cast and reinject at the new location to occlude a large AVM without filling the draining veins (Regine et al, 2015 ). A prior study has reported reflux of EVOH within the afferent artery during embolization of high flow AVM and nontarget embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Other rare off-label uses of EVOH include embolization of gastrointestinal hemorrhage (Urbano et al, 2014 ), post-traumatic hemorrhage (Müller-Wille et al, 2011 ), type I endoleaks (Eberhardt et al, 2014 ), pulmonary hemorrhages (Bommart et al, 2011 ; Izaaryene et al, 2016 ), pseudoaneurysms (PSAs) (Vanninen & Manninen, 2007 ), pelvic AVMs (Castaneda et al, 2002 ; Wohlgemuth et al, 2015 ), and neoplasms. (Regine et al, 2015 ) The existing literature is in the form of case reports or series. The possible reasons for the slow adoptation of this agent in the treatment of peripheral pathologies could be secondary to its perceived technical complexity, inadequate training, feared complications, high cost and lack of data demonstrating its efficacy and safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchial artery embolization (BAE) was first described by Rémy et al in 1973 [ 3 ], and it is now considered a first-line treatment for most cases of massive hemoptysis [ 4 , 5 ]. The technique performed in the above seven cases is a new technique of embolization after deployment of a stent in the bleeding artery.…”
Section: Discussionmentioning
confidence: 99%